Decreasing The Effective Communication Of The Existence Of Implementing The Tradition Of Gugur Gunung ( Sambatan Gawe Omah) In The Community - Diah Nadiatul Jannah; Basid Elmi Izzaqi; Wildan Fadlillah; Supardi Supardi; Sudrajat Sudrajat (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2023)
Sambatan Gawe Omah is one of the traditions of the Gunungkidul people whose implementation cannot be separated from the way the local community uses it as a means of communication. This study examines the tradition of splice gawe omah as a form of effective communication which has experienced a decline. The aims of this study were 1) to find out the position of the gawe Omah splice in Autumn Gunung, 2) to analyze the forms of effective communication in the gawe Omah splice tradition, 3) to find out the decline in effective communication in the gawe Omah splice tradition. This study uses a qualitative method through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that there is a decrease in effective communication in the  Sambatan Gawe Omah tradition due to high secondary relationships with the community, the reciprocal principle that brings the community physically present but not empathetically, and the strengthening of personal interest in building houses so that workmanship specifications are needed.